Analisis Instalasi Jaringan Internet Desa Karangjati - Pudji Widodo; Suleman Suleman; Bambang Kelana Simpony (LPPM STIKI MALANG, 2023)
Advances in information technology are currently growing very rapidly in line with the human need to access information quickly, easily and accurately. The Internet network is one of the tools to meet these information needs. BUMDesa of Karangjati Village creates a small village-owned server that is intended to facilitate the community's Internet needs at a more affordable price than the prices of other internet service providers. The research was conducted to observe and improve the network topology, so as to maximize the internet network belonging to BUMDesa Karangjati Village. In addition, research is conducted to solve problems such as running out of ports when there are additional subscribers or overcoming user modems that are often interrupted by replacing a problematic modem adapter or replacing an old modem with a new modem. The method used is by conducting direct observations and interviews with BUMDesa Jati Lestari Karangjati Village. The proposed configuration scheme is created using the Cisco Packet Tracer simulation application. Based on the results of internet research owned by BUMDesa Karangjati Village, it uses a tree topology because there is only one central server and the IP address address configuration uses class C, because it still uses a network on a small scale. The transmission medium uses a fiber optic cable from the server and the addition of ports will continue to be carried out in line with the increase in internet network subscribers.